The Evaluation of the Tube Current Impact on Axial, Sagittal, and Coronal MTFs on CT Images Using an In-House Phantom (International Journal of Scientific Research in Science and Technology, 2024)
This study aims to evaluate an impact of tube current on modulation transfer functions (MTFs) from axial, sagittal, and coronal computed tomography (CT) images of an in-house phantom. An in-house phantom having three metal wires at x-, y-, and z-directions for 3D-MTF evaluation was scanned using GE Revolution EVO 128-slice CT scanner. The tube current was varied (i.e., 100, 200, and 300 mA). While other input parameters were kept constant (i.e., tube voltage of 120 kV, slice thickness of 0.625 mm, rotation time of 1 s). The measurements of MTF were performed automatically using IndoQCT software. MTFs in the x-axis were measured from axial images. MTFs in z-axis were measured from sagittal and coronal images (They were reformatted from axial images using a cubic interpolation). The mean values of 10%-MTF for 100 mA in axial, sagittal and coronal images were 0.70 ± 0.00, 0.69 ± 0.00 and 0.67 ± 0.01 mm-1, respectively. The mean values of 10%-MTF for 200 mA in axial, sagittal and coronal images were 0.71 ± 0.00, 0.69 ± 0.00 and 0.67 ± 0.00 mm-1, respectively. The mean values of 10%-MTF for 300 mA in axial, sagittal and coronal images were 0.70 ± 0.00, 0.69 ± 0.01 and 0.68 ± 0.00 mm-1, respectively. Tube current has no obvious impact on MTF values in the x- and z-axis from axial, sagittal, and coronal images.